2022
DOI: 10.1021/acsami.2c08270
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Mechanical Metamaterials with Tailorable Negative Poisson’s Ratio and Arbitrary Thermal Expansion in Multiple Thermal Deformation Modes

Abstract: Mechanical metamaterials pave a way for designing and optimizing microstructure topology to achieve counterintuitive deformation including negative Poisson’s ratio (NPR) and negative thermal expansion (NTE). Previous studies were always limited to single anomalous mechanical or thermal deformation, but current applications for high-precision mechanical or optical equipment always require their combination and customized and anisotropic deformation parameters. This work develops programmable two-dimensional (2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 45 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…Under the external stimulus, the shape, property or function of the object will change with time. Stimulus-responsive shape memory materials based on 4D printing have the advantages of simple manufacturing process, large SMMs have gradually become a new protagonist in the field of materials and have been endowed with richer functional properties, including reconfigurable [65, 66], programmable [67], elastic wave propagation control [68,69] and mechanical computing [70,71]. et al In the future, the functional properties of natural materials will gradually diminish.…”
Section: Smart Mechanical Metamaterialsmentioning
confidence: 99%
“…Under the external stimulus, the shape, property or function of the object will change with time. Stimulus-responsive shape memory materials based on 4D printing have the advantages of simple manufacturing process, large SMMs have gradually become a new protagonist in the field of materials and have been endowed with richer functional properties, including reconfigurable [65, 66], programmable [67], elastic wave propagation control [68,69] and mechanical computing [70,71]. et al In the future, the functional properties of natural materials will gradually diminish.…”
Section: Smart Mechanical Metamaterialsmentioning
confidence: 99%
“…More recent efforts aim to tackle this issue with a heavier focus on developing new classes of structure-dominated materials and in particular active metamaterials [15] [16] [17]. Metamaterials exhibit usual characteristics while excited by external perturbations, such as negative properties [18] [19] [20] [21], ultra-properties [22] [23] [24] and extremal properties [25] [26] [27]. They have gained significant attention due to their potential to serve as novel micro-engineered platforms to achieve multifunctionality.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of mechanical metamaterials, researchers have observed that metamaterials prepared by designing structures exhibit better energy absorption properties than single materials. Mechanical metamaterials are typically periodic assemblies of three-dimensional (3D) lattices designed to exhibit exceptional mechanical properties, such as lightweight, high specific stiffness, high specific strength, negative Poisson’s ratio, , excellent energy-absorbing capacity, , and impact resistance . The rapid development of additive manufacturing (AM) technology has facilitated the design and fabrication of complex lattice metamaterials, including honeycomb structures, octet truss, octahedrons, body-centered cubes (BCCs), , face-centered cubes (FCCs), and chiral structures .…”
Section: Introductionmentioning
confidence: 99%